AB0041 B-cell activating factor (BAFF) binding receptors (BBR) on B cells: characterization in patients with rheumatoid arthritis (RA) receiving anti-TNF-alpha agent infliximab (IFX). (23rd January 2014) - Hernández, D.; de la Torre, I.D.; Cambridge, G.; Martinez, L.; Nieto, J.C.; Ovalles, J.; Barrios, J.; González, C.; Montoro, M.; Lόpez-Longo, J.; Monteagudo, I.; Carreño, L.; et al.
Abstract : Objectives: To evaluate BBR (BAFF-R, TACI and BCMA) expression on B-cells in response to the treatment with the anti-TNF-alpha agent infliximab in RA patients Methods: We assessed naïve and memory B-cells expressing BBR in peripheral blood in 23 patients with RA on infliximab treatment: 12 in no-remission (DAS28>3.2), 11 in remission (DAS28<2.6) and healthy controls (HC; n=12) using monoclonal antibodies to CD19, CD27, IgD, CD38, BAFF-R, TACI and BCMA by multiparametric flow cytometry. Results: Despite similar BAFF-R expression on naïve and memory B-cells of RA patients (remission/no-remission) compared to HC, we found increased % of CD27+ memory B-cells TACI+ in RA patients (remission/non remission) compared to HC (p=0.004 and p=0.01, respectively). A significantly lower % of B-cells expressed BCMA on naive population for both remission/ no-remission RA patients vs. HC (naïve mature, CD19+IgD++CD38-, p=0.01 and p=0.001, respectively, naïve transitional CD19+IgD+, CD38++, p=0.0007 and p=0.01, respectively) and on memory population only for RA patients in remission compared to HC (plasmablast CD19+IgD-CD38 p=0.03, and post-GC memory CD19+, IgD-CD38++, p=0.04). Conclusions: Major BBR alterations are present in RA patients treated with the anti-TNF agent infliximab; blocking TNF-alpha could restore partly the defect on the maturation-survival process in RA patients B-cells, down-regulating BCMA and preventing short lived B-cells from becoming antibody-producing plasma cells. However, RA patients on anti-TNF therapy show a increased TACI and decreased BCMA expression in memory B-cells; defects in B-cell pool might persist due to contributions by other soluble and/or cellular mediators. Disclosure of Interest: None Declared